Preparation of chemically treated sugarcane bagasse fiber reinforced epoxy composites and their characterization. Issue 1 (1st January 2019) - Vidyashri, V.; Lewis, Henrita; Narayanasamy, P.; Mahesha, G T; Bhat, K. Subrahmanya
Abstract: Bagasse fiber which is abundantly available as waste after processing of sugarcane is used as reinforcement with an epoxy polymer in forming the natural fiber reinforced composites. The raw fibers were treated chemically to improve compatibility and adhesion with the epoxy polymer. Treated and untreated fibers were subjected to analysis such as Scanning Electron Microscopy (SEM), X-Ray Diffraction (XRD) and Thermogravimetric Analysis (TGA) to understand the structural changes and to determine thermal stability. The mechanical properties of fibers and the composites were evaluated by conducting tensile tests. The results reveal alkaline pretreated and KMnO4 treated fibers show improved mechanical and thermal properties.